2021
DOI: 10.1016/j.jacc.2021.03.314
|View full text |Cite
|
Sign up to set email alerts
|

Fat-Secreted Ceramides Regulate Vascular Redox State and Influence Outcomes in Patients With Cardiovascular Disease

Abstract: Background Obesity is associated with increased cardiovascular risk; however, the potential role of dysregulations in the adipose tissue (AT) metabolome is unknown. Objectives The aim of this study was to explore the role of dysregulation in the AT metabolome on vascular redox signaling and cardiovascular outcomes. Methods A screen was conducted for metabolites differentially secreted by thoracic AT (ThAT) and subcutaneous AT in obese patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 20 publications
3
71
0
Order By: Relevance
“…Interestingly, in the present study, subjects with a former myocardial infarction were found having increased levels of glycoceramides at baseline, lending support to the notion of an association between ceramides and atherosclerosis. Recently, it was demonstrated that fat-secreted ceramides are modifiable regulators of vascular redox state with a direct impact on CV mortality in people with atherosclerosis and that liraglutide was a potential drug target to decrease the risk [ 10 ]. It was also recently found that accumulation of ceramides associates with de novo lipogenesis and insulin resistance leading to low-grade inflammation [ 33 ], which, in turn, is suggested to increase the risk of T2D and CV disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in the present study, subjects with a former myocardial infarction were found having increased levels of glycoceramides at baseline, lending support to the notion of an association between ceramides and atherosclerosis. Recently, it was demonstrated that fat-secreted ceramides are modifiable regulators of vascular redox state with a direct impact on CV mortality in people with atherosclerosis and that liraglutide was a potential drug target to decrease the risk [ 10 ]. It was also recently found that accumulation of ceramides associates with de novo lipogenesis and insulin resistance leading to low-grade inflammation [ 33 ], which, in turn, is suggested to increase the risk of T2D and CV disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MS data processing was performed using open-source software MZmine 2.53 [ 10 ]. Quantitation of the following metabolites (aspartic acid, glutamic acid, isoleucine, methionine, fumaric acid, malic acid, leucine, valine, glycerol-3-phosphate, alanine, threonine, 3-hydroxybutyric acid, isocitric acid, arachidonic acid, glutamine, lactic acid, linoleic acid, oleic acid, palmitic acid, stearic acid and lysine, beta-muricholic acid (b-MCA), cholic acid (CA), chenodeoxycholic acid (CDCA), deoxycholic acid (DCA), glycocholic acid (GCA), glycochenodeoxycholic acid (GCDCA), glycodeoxycholic acid (GDCA), glycohyocholic acid (GHCA), glycohyodeoxycholic acid (GHDCA), glycolitocholic acid (GLCA), glycoursodeoxycholic acid (GUDCA), hyocholic acid (HCA), hyodeoxycholic acid (HDCA), lithocholic acid (LCA), tauro-alpha/beta-muricholic acid (Ta,bMCA), taurocholic acid (TCA), taurochenodeoxycholic acid (TCDCA), Taurodeoxycholic acid (TDCA) taurodehydrocholic acid (TDHCA), trihydroxycholestanoic acid (THCA), taurohyodeoxycholic acid (THDCA), taurolitocholic acid (TLCA), tauroursodeoxycholic acid (TUDCA), tauro-omega-muricholic acid (TwMCA), ursodeoxycholic acid (UDCA), omega/alpha-muricholic acid (w/a-MCA) was done using authentic standards at six different concentrations, other metabolites were determined semi-quantitatively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a cardiovascular perspective, ceramides located at the surface of LDL drive their transcytosis through the endothelium and uptake into macrophages, which results in foam cell formation, vascular inflammation, and atherosclerosis [40][41][42]. Thoracic adipose tissue of obese individuals secretes a particular ceramide species, named Cer (18:1;2/16:0), which acts on endothelial cells to reduce vasodilatation, induce inflammation, oxidative stress, and finally increase risk of cardiovascular death [55]. Again, circulating long-chain ceramides, such as Cer (18:1;2/16:0), Cer (18:1;2/18:0) and Cer (18:1;2/24:1), seem to be the species most frequently associated with cardiovascular morbidity and mortality [10,31,56].…”
Section: Ceramides In Cardiometabolic Health and Diseasesmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death worldwide ( 1 ). Vascular diseases, particularly atherosclerosis, are initiated at an early stage in life and remain asymptomatic for a long period until they reach advanced stages ( 2 ). Among vascular diseases, atherosclerosis is a pathologic process of lipid accumulation, scarring, and inflammation in the vascular wall, particularly the subendothelial (intimal) space of arteries, which leads to vascular wall thickening, luminal stenosis, and calcification ( 3 ).…”
Section: Introductionmentioning
confidence: 99%